Montaigne's Unruly Brood Textual Engendering and the Challenge to Paternal Authority. - Regosin, Richard L. (University of California Press, 2020)
Perhaps as old as writing itself, the metaphor of the book as child has depicted textuality as an only son conceived to represent its father uniformly and to assure the integrity of his name. Richard L. Regosin demonstrates how Montaigne's Essais both departs from and challenges this conventional figure of textuality. He argues that Montaigne's writing is best described as a corpus of siblings with multiple faces and competing voices, a hybrid textualit.